Securing Health Data in the Digital Age: Challenges, Regulatory Frameworks, and Strategic Solutions in Saudi Arabia - Alhoussari, Houda (Journal of Ecohumanism, 2025)
The rapid digital transformation in Saudi Arabia, driven by the ambitious Vision 2030 initiative, positions health data as a cornerstone of innovation in the healthcare sector. Health data, classified as sensitive and strategic, is critical for improving patient care, advancing medical research, and fostering predictive analytics. However, this digitization also exposes health data to escalating cyber threats, such as ransomware, phishing, and attacks on IoMT devices. These risks compromise data confidentiality, integrity, and availability, eroding trust and causing significant economic impacts. This study adopts an analytical and comparative approach to evaluate the challenges and solutions associated with health data cybersecurity in Saudi Arabia. It examines the strengths and weaknesses of national frameworks, including the Personal Data Protection Law (PDPL) and the Essential Cybersecurity Controls (ECC), while benchmarking them against international standards such as the General Data Protection Regulation (GDPR) and the Health Insurance Portability and Accountability Act (HIPAA). By addressing technical, organizational, and human challenges, the research proposes strategic recommendations, emphasizing technological measures, regulatory enhancements, and capacity-building initiatives. The findings aim to contribute to the development of a secure and innovative digital healthcare ecosystem in Saudi Arabia, aligning with the goals of Vision 2030 and ensuring the protection of sensitive health data.